(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Alexander Arkadyevich Fainberg (1939-2009) is one of the poets who played an important role in Uzbek and Russian literature of the 20th century. He was a creator who successfully worked in poetry, translation, and screenwriting. In the poet’s works, themes such as human soul, freedom, homeland, nature, and spiritual responsibility are deeply philosophically explored. Fainberg’s creativity stands out for its sincerity, richness of symbolic meaning of images, and expression of complex relationships between man and nature.